Kako išče Google? - Kramar Fijavž, Marjeta (Obzornik za matematiko in fiziko, 2014)
We present the main idea of the PageRank algorithm which is the core of the Google search engine. We concentrate on the theoretical background of the algorithm and prove its convergence in two different ways, by the Perron-Frobenius theory for positive matrices and using Banach fixed point theorem.
Keywords: spletni iskalniki; algoritem PageRank; pozitivne matrike; izrek o negibni točki